Detection of biomarker p53 mutated gene by a silicon nanowire nanosensor. (8th April 2013) - Pham, Van Binh; Thi, Hien Le; Pham, Xuan Thanh Tung; To, Van Vinh; Dang, Ngoc Thuy Duong; Le, Thi Thanh Tuyen; Nguyen, Viet Long; Le, Van Thao; Bui, Truong Giang; Dang, Mau Chien; Tong, Duy Hien
Among biosensors of various types, the silicon nanowire field–effect transistor (SiNW–FET) is believed to be the most sensitive and powerful device for bio–applications. In fact, these devices have demonstrated the ability to detect a variety of analyses such as particular DNA sequences, cancer biomarkers and larger entities such as viruses. The principle of sensing is based on the variation of conductivity resulting from a disturbance of charge on the surface of the SiNW–FET. In this study, we have used two different processes for surface modification of silicon nanowire. As the DNA of liver cancer cells has mutation at codon 249 which changes one base guanine (G) by base thymine (T), we thus designed 17–mer DNA oligonucleotides, which were used as a receptor to capture the DNA of p53 mutated gene. The fabricated SiNW biosensor could detect DNA of p53 mutated gene with concentrations down to about 100 pM.